PLANT GROWTH PROMOTING RHIZOBACTERIA- IMPACTS ON CAULIFLOWER YIELD AND SOIL HEALTH - KAUSHAL, MANOJ; KAUSHAL,; RAJESH (The Bioscan, 2013)
The present investigation were conducted for two summer seasons during 2009 and 2010 in the field of Department of Soil science and Water Management, Dr. Y. S. Parmar University of Horticulture and Forestry, Nauni, Solan, Himachal Pradesh to study the effects of integrated nutrient management systems on growth, yield of cauliflower and soil health. The conjoint effect of plant growth promoting rhizobacteria (PGPR) at varying (50%, 75% and 100%) doses N and P fertilizers registered a significant increase in number of non-wrapper leaves, curd diameter, curd depth and curd weight of cauliflower, total microbial counts and available N and P contents of soil. The application of MK5 isolate at 75% recommended dose of NP fertilizers not only increased the yields of cauliflower by 24% but also saved 31kg N /ha and 8 kg P/ha fertilizers over control (recommended doses of NPK). A significant increase in available N and P contents were also noted by the conjoint application of PGPR and chemical fertilizers. Hence the developed integrated nutrient module can be used for enhanced yields without destructing soil health in mid hills of North Western Himalayas.